Perbedaan Penggunaan Minyak Zaitun dan Minyak VCO (Virgin Coconut Oil) dengan Kejadian Strie Gravidarum pada Ibu Nifas Hari 1-7 - Yuli Irnawati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Striae gravidarum can be reduced by the use of olive oil.. 100 g of extra virgin oil contains 14.39 mcg alpha tocopherol. Whereas the coconut oil in 100 g only contains 0.1 mg of Vitamin E. The purpose of this study was to analyze the difference between the use of olive oil and coconut oil on the incidence of strie gravidarum in pregnant women. This research is included in experimental research. All pregnant women in January to August were 30 pregnant women. The sample in this study were 15 pregnant women who used olive oil and 15 pregnant women who used VCO oil. The mean value of Strie Gravidarum in postpartum mothers given Olive oil is 3.13 in a day and the standard deviation is 1,642. While the mean value (mean) of Strie Gravidarum in postpartum mothers who were given VCO oil was 2.93 in a day and the standard deviation was 1.831. Statistical test results with independent sample t test obtained p-value = 0.007 (p-value<a = 0.05), these results indicate that there are significant differences between the administration of olive oil and VCO oil to striae gravidarum in postpartum mothers.